2015
DOI: 10.1016/j.jcat.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Selective oxidation and oxidative dehydrogenation of hydrocarbons on bismuth vanadium molybdenum oxide

Abstract: a b s t r a c tA systematic investigation of the oxidative dehydrogenation of propane to propene and 1-and 2-butene to 1,3-butadiene, and the selective oxidation of isobutene to methacrolein was carried out over Bi 1Àx/3 V 1Àx Mo x O 4 (x = 0-1) with the aim of defining the effects of catalyst and reactant composition on the reaction kinetics. This work has revealed that the reaction kinetics can differ significantly depending on the state of catalyst oxidation, which in turn depends on the catalyst compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 44 publications
3
34
0
Order By: Relevance
“…According to the group of Keulks [8,20], re-oxidation of the catalyst is the rate-determining step in propylene oxidation at temperatures below 400 °C, whereas abstraction of an α-hydrogen atom to form an allylic intermediate is the rate determining step at higher temperatures (>400 °C), in agreement with theory [14]. Recently, it was further reported that the reaction order in oxygen was zero at 340 °C and 400 °C for Bi2Mo3O12 catalysts, i.e., the reaction rate for acrolein formation, was independent of the partial pressure of oxygen, indicating that the transition temperature where re-oxidation of the catalyst becomes the rate determining step was lower than 340 °C [61,62]. The hydrothermally synthesized samples at pH = 4-8 exhibited high propylene conversion and also relatively high acrolein selectivities already at 360 °C.…”
Section: Catalytic Performance In Propylene Oxidation To Acroleinsupporting
confidence: 84%
“…According to the group of Keulks [8,20], re-oxidation of the catalyst is the rate-determining step in propylene oxidation at temperatures below 400 °C, whereas abstraction of an α-hydrogen atom to form an allylic intermediate is the rate determining step at higher temperatures (>400 °C), in agreement with theory [14]. Recently, it was further reported that the reaction order in oxygen was zero at 340 °C and 400 °C for Bi2Mo3O12 catalysts, i.e., the reaction rate for acrolein formation, was independent of the partial pressure of oxygen, indicating that the transition temperature where re-oxidation of the catalyst becomes the rate determining step was lower than 340 °C [61,62]. The hydrothermally synthesized samples at pH = 4-8 exhibited high propylene conversion and also relatively high acrolein selectivities already at 360 °C.…”
Section: Catalytic Performance In Propylene Oxidation To Acroleinsupporting
confidence: 84%
“…It might be, therefore, possible that different mechanisms contribute to acrolein formation over 6 V/SBA‐15, such as a low‐temperature (200–300 °C) oxidation pathway catalyzed by activated oxygen species at the surface, such as peroxovanadate, via propylene oxide as intermediate followed by oxidative dehydrogenation (Scheme a), and the allylic oxidation of propylene at higher temperatures (>300 °C) (Scheme b). In the low‐temperature range acetone and propionaldehyde may be formed as isomerization products of propylene oxide . Indication of the participation of peroxide species in oxidative dehydrogenation of propane over supported vanadium oxide catalysts has been found recently by experiment, and theory .…”
Section: Resultssupporting
confidence: 74%
“…Low amounts of butane and butadiene were detected at low CO 2 -to-butane molar ratios despite the fact that C-H bond dissociation can occur on the molybdenum metal. 38 In the presence of CO 2 , significant amounts of hydrogen and CO are formed. Aside from a dehydrogenation reaction, a CO 2 reforming reaction can also take place.…”
Section: Oxidant-to-butane Ratiomentioning
confidence: 99%
“…The oxidative dehydrogenation of n-butane to butenes and 1,3-butadiene follows the Mars-van Krevelen mechanism, as also reported by several researchers. 2,7,8,38 In this mechanism, chemisorption of n-butane, activation of C-H bonds, and abstraction of hydrogen from n-butane to form an alkyl radical-metal cation intermediate are important steps in the oxidative dehydrogenation of n-butane. 27,49,50 The rates of ODH are enhanced if the cation present in the catalyst is a weak acid and can be reduced by two electrons transferred from C-H bonds.…”
Section: Mars-van Krevelen Mechanismmentioning
confidence: 99%